2014
DOI: 10.1074/jbc.m114.587295
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of Mitogenic Signaling Networks in the Human Placenta

Abstract: Placental cell growth depends on an adaptable combination of an endogenous developmental program and the exogenous influence of maternal growth factors, both of which may be influenced by microRNA (miR)-dependent effects on gene expression. We have previously shown that global miR suppression in placenta accelerates proliferation and enhances levels of growth factor signaling mediators in cytotrophoblast. This study aimed to identify miRs involved in regulating placental growth. An initial array revealed 58 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 48 publications
(52 reference statements)
3
44
0
Order By: Relevance
“…Suppressed cell migration and cancer invasion has also been reported, which suggests that miR-145 may function as a tumor suppressor (30). The results of the present study are in accordance with those of a previous study that indicated that miR-145 is a positive regulator of endogenously regulated trophoblast expansion (19). Genes associated with trophoblast invasion include heme oxygenase-1, epidermal growth factor (EGF), VEGF and MUC1 (21,31,32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Suppressed cell migration and cancer invasion has also been reported, which suggests that miR-145 may function as a tumor suppressor (30). The results of the present study are in accordance with those of a previous study that indicated that miR-145 is a positive regulator of endogenously regulated trophoblast expansion (19). Genes associated with trophoblast invasion include heme oxygenase-1, epidermal growth factor (EGF), VEGF and MUC1 (21,31,32).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that miR-145 may be able to regulate the expression of sex determining region Y-box 2 and influence the proliferation and invasion ability of JAR and JEG-3 cells in the development of human choriocarcinomas (18,19). Mucin (MUC1) is a type 1 transmembrane protein that serves a vital role in trophoblast cell proliferation and migration (20).…”
Section: Introductionmentioning
confidence: 99%
“…The miR-let-7 family has also been shown to inhibit oxidized LDL uptake and apoptosis of endothelial cells [36,37]. In the placenta, let-7a has been shown to reduce cytotrophoblast proliferation [38]. Polymorphisms in let-7 have been associated with increased risk of T2DM [39].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that miR-145 is important in mediating placental growth in humans (Farrokhnia et al, 2014;Forbes et al, 2012). One of the targets of miR-145 is the type-1 insulin-like growth factor receptor (IGF1R) (La Rocca et al, 2009;Law et al, 2012) and IGF1R mRNA has been previously shown to be present in endometrium (Zhou et al, 1994).…”
Section: Introductionmentioning
confidence: 99%